The Effect Of E-Wom, Price And Service Quality On Purchasing Decisions Mediated By Marketing Strategy (Thrift Shop Empirical Study On Tiktok Social Media) - Marcellino, Yeremia; Pardede, Ratlan (Publikasi Indonesia, 2023)
This study aims to determine the effect of EWOM, Price, and Service Quality on purchasing decisions mediated by marketing strategy (thrift shop empirical study on Tik Tok Social Media). The research data was obtained from distributing questionnaires via the Google form by providing twenty questions. Samples were taken using a purposive sampling technique with a total of 220 respondents. This research was distributed in the Banten area, namely Tangerang Regency, Tangerang City and South Tangerang by looking at the high level of internet usage. This study uses quantitative analysis techniques and is processed using AMOS. The purpose of this study is to see how EWOM, price and service quality can influence purchasing decisions. The results of this study indicate that EWOM and service quality have a positive and significant influence on purchasing decisions. However, Price do not have a positive and significant influence on purchasing decisions.